Comparative studies on the phylogeny and systematics of the rhabditidae (Nematoda) - Sudhaus, W.; Fitch, D. (Journal of Nematology, 2001)
Indigenous communities of soil-resident nematodes have a high potential for soil healthassessment as nematodes are diverse, abundant, trophically heterogeneous and easilyextractable from soil. The conserved morphology of nematodes is the main operationalreason for their under-exploitation as soil health indicators, and a user-friendly biosensorsystem should preferably be based on nonmorphological traits. More than 80% of the mostenvironmental stress-sensitive nematode families belong to the orders Mononchida andDorylaimida. The phylogenetic resolution offered by full-length small subunit ribosomalDNA (SSU rDNA) sequences within these two orders is highly different. Notwithstandingseveral discrepancies between morphology and SSU rDNA-based systematics, Mononchidafamilies (indicated here as M1–M5) are relatively well-supported and, consequently, family-specific DNA sequences signatures could be defined. Apart from Nygolaimidae and Longi-doridae, the resolution among Dorylaimida families was poor. Therefore, a part of the morevariable large subunit rDNA (≈ 1000 bp from the 5′-end) was sequenced for 72 Dorylaimidaspecies. Sequence analysis revealed a subclade division among Dorylaimida (here definedas D1–D9, PP1–PP3) that shows only distant similarity with ‘classical’ Dorylaimid system-atics. Most subclades were trophically homogeneous, and — in most cases — specificmorphological characteristics could be pinpointed that support the proposed division. Toillustrate the practicability of the proposed molecular framework, we designed primersfor the detection of individual subclades within the order Mononchida in a complex DNAbackground (viz. in terrestrial or freshwater nematode communities) and tested them inquantitative assays (real-time polymerase chain reaction). Our results constitute proof-of-principle for the concept of DNA sequence signatures-based monitoring of stress sensitivenematode families in environmental samples.
NeMys doc_id: 14981 from NeMys